Evolutionary analysis of genes coding for Cysteine-RIch Secretory Proteins (CRISPs) in mammals - Arévalo, Lena (2020)
Cysteine-RIch Secretory Proteins (CRISP) are expressed in the reproductive tract of mammalian males and are involved in fertilization and related processes. Due to their important role in sperm performance and sperm-egg interaction, these genes are likely to be exposed to strong selective pressures, including postcopulatory sexual selection and/or male-female coevolution. We here perform a comparative evolutionary analysis of Crisp genes in mammals. Currently, the nomenclature of CRISP genes is confusing, as a consequence of discrepancies between assignments of orthologs, particularly due to numbering of CRISP genes. This may generate problems when performing comparative evolutionary analyses of mammalian clades and species. To avoid such problems, we first carried out a study of possible orthologous relationships and putative origins of the known CRISP gene sequences. Furthermore, and with the aim to facilitate analyses, we here propose a different nomenclature for CRISP genes (EVAC1-4, "EVolutionarily-analyzed CRISP") to be used in an evolutionary context.